Bringing the Field to the Supervisor: Innovation in Distance Supervision for Field-Based Experiences Using Mobile Technologies. (March 2015) - Schmidt, Matthew; Gage, Ashley MacSuga; Gage, Nicholas; Cox, Penny; Mcleskey, James
This paper provides a summary of the design, development, and evaluation of a mobile distance supervision system for teacher interns in their field-based teaching experiences. Developed as part of the University of Florida's Restructuring and Improving Teacher Education 325T grant project, the prototype system streams video of teachers in rural classrooms using iPad Minis equipped with a variety of peripheral devices to provide enhanced optics and multi-source audio. A description of the prototype, including hardware and software components, is provided.